2022
DOI: 10.1002/csr.2326
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, Social, Governance scores and the Missing pillar—Why does missing information matter?

Abstract: Environmental, Social, and Governance (ESG) scores measure companies' performance concerning sustainability and are organized in three pillars: Environmental, Social, and Governance. These complementary non‐financial ESG scores should provide information about companies' ESG performance and risks. However, the extent of not yet published ESG information makes the reliability of ESG scores questionable. To explicitly capture the not yet published information on ESG category scores, a new pillar, the so‐called M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Both data sets are similar in size, however, the US data exhibits stronger average kurtosis as shown in Table 1. Additionally, we find that the ESG scores of both data sets improve over time as companies are under pressure to improve their ESG performance and continue to disclose more information (see Table 2 and Figure 1) (Sahin et al, 2022).…”
Section: Data Description and Empirical Set-upmentioning
confidence: 84%
See 1 more Smart Citation
“…Both data sets are similar in size, however, the US data exhibits stronger average kurtosis as shown in Table 1. Additionally, we find that the ESG scores of both data sets improve over time as companies are under pressure to improve their ESG performance and continue to disclose more information (see Table 2 and Figure 1) (Sahin et al, 2022).…”
Section: Data Description and Empirical Set-upmentioning
confidence: 84%
“…The key message is that improvements in terms of ESG performance might lead to lower risk and more stable markets, while instead, companies in the lower ESG classes might contribute the most to systemic risk. Therefore, it is important to support disclosure policies of non-financial information, as ESG class D stocks typically are characterized by a lack of infrastructure and missing information (see Sahin et al, 2022) as well other policies, such as tax incentives, which stimulate companies to increase their efforts and investments in ESG-related activities, this resulting in improved ESG scores. By doing so, information on company characteristics, both financial and non-financial, would increase, providing further insights and knowledge, which we expect to lead to improved overall economic and financial stability, making the system less vulnerable even in times of turmoil.…”
Section: δQl-covarmentioning
confidence: 99%
“…47 The way ESG scores are calculated and their impact on the financial performance or risk vary depending on the sector, topic, provider, and country. 48,49,50 Another important research study could analyze the dependence structure of the assets' ESG disclosure quality on various topics. It would highlight what seems important to disclose in ESG-related topics for companies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the notion of negative screening is straightforward, our review found that implementing negative screens typically requires additional research efforts. Firstly, given the presence of discernible ESG rating disagreement (Berg et al, 2022;Chatterji et al, 2016;Sahin et al, 2022), investors may exclude different firms based on which rating agencies they consult with. The presence of ESG rating disagreement also affects how investors identify involvement in controversial business operations.…”
Section: Jal 462mentioning
confidence: 99%